MERS: emergence of a novel human coronavirus - Raj, V Stalin (Elsevier B.V., 2014)
A novel coronavirus (CoV) that causes a severe lower respiratory tract infection in humans, emerged in the Middle East region in 2012. This virus, named Middle East respiratory syndrome (MERS)-CoV, is phylogenetically related to bat CoVs, but other animal species like dromedary camels may potentially act as intermediate hosts by spreading the virus to humans. Although human to human transmission has been demonstrated, analysis of human MERS clusters indicated that chains of transmission were not self-sustaining, especially when infection control was implemented. Thus, timely identification of new MERS cases followed by their quarantine, combined with measures to limit spread of the virus from the (intermediate) host to humans, may be crucial in controlling the outbreak of this emerging CoV.